Pengaruh Profitabilitas, Solvabilitas dan Rasio Pasar terhadap Harga Saham pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Erica Sesiana Br Panggabean; Halomoan Nathanael Joshua Akita; Khomeiny Yunior (Universitas Negeri Surabaya, 2023)
When it comes to a country's economic development and stability, banking, the beating heart of the global economy, plays a crucial role. Therefore, many existing and potential investors are attracted to invest in this industry. But before jumping into the capital market, investors need to pay attention to several factors, including a thorough examination of the company's financial statements. This study will examine the relationship between profitability, solvency, and market ratios seen in banking businesses' financial statements and stock prices. Purposive sampling was utilized to acquire data from 47 of the financial institutions included in the IDX for the years 2018-2021. The hypotheses were evaluated by a battery of tests employing linear regression analysis. Hypothesis testing reveals that profitability, solvency, and market ratios all have an impact on the stock prices of Indonesia Stock Exchange-listed banking businesses from 2018 to 2021. (simultaneously). Then, throughout the 2018-2021 time, the market ratio to stock prices of IDX-listed banking firms has a positive and substantial influence on stock prices, while the profitability and solvency of IDX-listed banking companies have a negative and large effect on stock prices.